Penelitian Konsep Bisnis Nature Home Decor - Tiffany Aglesia; Ellen Saputra (Jurnal Vicidi, 2018)
Research of Nature Home Decor business concept is conducted with the purpose to define the programming process of Nature Home Decor to sell decorations product made from eco-friendly and natural material combined with living plants design, including carnivores and cactus. Home decorations made of natural materials also tend to have more functionalities in urban living. The sole purpose of idea creation of this business is to focus on the increase of business and industry in urban living, which renders a negative impact towards ecosystem, especially plants. With the intention to render parts of plant ecosystem to be more functional and to have good impact on urban living. Research method used for this project is with qualitative conducted by interviews and quantitative conducted by distribution of questionnaires. The conclusion of research is that urban society is interested of Natural Home Decor products for urban living applications. In addition, form and colors also give big influence to make the products look more attractive and minimalist.